Evaluation of wheat in rations for growing-finishing swine - Tribble, L.F.; Jensen, A.H.; Deyoe, C.W.; Pfost, H.B. (Kansas Agricultural Experiment Station, 2011)
A series of experiments has further evaluated wheat as swine feed. The experiments were conducted in confinement on concrete floored pens. Purebred Duroc, Poland and D x P crossbred pigs were used in all trials. All rations were supplemented with calcium, phosphorus, salt, trace minerals, the following vitamins A. D. riboflavin, pantothenic acid, niacin, choline, B 12 and antibiotic, chlortetracycline. Soybean oil meal was added to the grain to bring protein content to the desired level.
Keywords: Swine; Sorghum grain; Gain; Corn; Performance